Porcine ear necrosis in nursery piglets is preceded by oral manipulations of the ear - Mateusz Malik; Koen Chiers; Ilias Chantziaras; Dominiek Maes (Porcine Health Management)
Abstract Background Porcine ear necrosis (PEN) is characterized by dry crusts on the ear tip. The crusts often progress to moist and bloody lesions and may lead to partial loss of the ear tissue. The cause and pathophysiology of PEN are unknown. Skin infections, systemic infections, or ear biting have been suggested as a cause of PEN, but no proper evidence has been shown. The behavioural factor has not yet been investigated, therefore this study evaluated the importance of oral manipulations in the occurrence of PEN in nursery pigs. Three farms affected by PEN were visited weekly, and the prevalence and severity were recorded. Video recordings of the animals were performed, and the behaviour was evaluated. The presence of pathogens in the lesions and histological alterations were also analysed. Results The highest percentage of pigs with PEN lesions in the farms ranged between 58 and 93%, with most lesions being of mild to moderate severity. The first ear lesions occurred about 1–2 weeks after an increase in the number of ear manipulations in the pens. The frequency of the ear manipulations clearly changed over time, and the number of oral ear manipulation behaviour significantly differed (P < 0.05) between pigs in pens with high and low PEN prevalence. Increased ear manipulation behaviour was significantly related to a subsequent increase in PEN lesions (OR = 4.3; P < 0.001). Metagenomic investigation of lesion scrapings revealed a variety of pathogens mostly with low abundance, where microscopic alterations were found mainly in the epidermis. Conclusions Oral manipulation of the ear pinnae by pen mates was followed by the development of PEN lesions one to two weeks later. This suggests that the behaviour played an important role in the PEN lesions formation in the nursery pigs of the three farms. Bacteria found in PEN lesions most probably were secondary to initial external skin damage, but their relevance needs to be investigated further.